A Deixis Analysis of Song Lyrics in “Here’s Your Perfect” by Jammie Miller - Damayanti, Ni Kadek Lisa Pratiwi (Jurnal Penelitian Mahasiswa Indonesia, 2023)
Language is not only used in oral or written form, furthermore, it also can be used in other fields such as song, movie, poetry, novel, and many more. One of the most popular media in the society that used to express any thoughts or feeling is song. Song is one of the system of communication in the world that use the combination of music and lyrics to express a feeling, idea, sense, and thought. Nowadays, many people love hearing songs. One element that become the main media to present ideas, feeling, or thought in song is lyrics. feeling, and emotion that influenced the readers such as the feeling of sad, happy, depressed, etc. There are many messages sent by the song composer to the listener through song lyrics. But sometimes, the listeners do not only try to understand the meaning of its lyrics but they also will try to find the meaning of the reader or the speaker means. In this study, the researcher wants to analyze deixis in song lyrics of Here’s Your Perfect by Jammie Miller. The aims of this study are to identify the kinds of deixis and to find the dominant types of deixis that are used in the song lyrics in Here’s Your Perfect.